Sliding discrete Fourier transform-based mono-component amplitude modulation–frequency modulation signal decomposition - Sumathi, Parasuraman; Singh, Ksh Milan (IET communications, 2015)
The sliding discrete Fourier transform-based phase locking scheme (SDFT-PLL) has been adapted for the extraction of message signals from mono-component amplitude modulation–frequency modulation (AM–FM) signals. In the proposed scheme, the SDFT-PLL is designed to track a carrier signal, which has been modulated by sinusoidal message signals both in amplitude and frequency. The sliding DFT filter is prone to windowing effect if input signal frequency drifts from centre carrier frequency. The amplitude and phase errors caused by this effect have been utilised to achieve locking condition by adaptive sampling frequency control. The SDFT-PLL is modified in such a way that the numerically controlled oscillator produces sampling pulses suitable for SDFTbin-1 and SDFT bin-0 for the retrieval of frequency and amplitude modulation signals, respectively. Hence, the frequency and amplitude variation of monocomponent AM–FM could be retrieved simultaneously. Furthermore, Bessel function-based analysis provides an insight to the removal of unwanted spectral components present in error signal. Simulation results prove the capability of PLL in message signal retrieval for large variation in frequency and amplitude. The proposed scheme is implemented in field programmable gate array to validate the performance of SDFT-PLL in decomposition of the mono-component AM–FM signal.